2004
DOI: 10.1016/j.sedgeo.2004.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Sand composition in an Iberian passive-margin fluvial course: the Tajo River

Abstract: The Tajo River, the 10th largest river in Europe, drains part of the western passive margin of Europe that includes multiple Province D is quartzofeldspathic (Qm55F39Lt6) with a dominance of phaneritic rock fragments (RssRg33Rm62) and corresponds to the lower reaches of the Tajo River, where siliciclastic deposits of the Neogene Santarem-Lisboa basin are the main sources.Sands plot on provenance-discrimination diagram (QmFLt) within the recycled-orogen field (Tajo River head) and continental block fields (uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Comparing these data with the average values obtained by Palomares and Arribas (1993) for different mixed source ar- rocks (Table 2) indicates a mixed composition source area (Mack, 1981). However, as several authors have suggested (Palomares and Arribas, 1993;Le Pera and Arribas, 2004), the abundance of these grains in the sediments is not directly related to their abundance in the source area. Even when each lithology have a different Sand Generation Index (Palomares and Arribas, 1993;Arribas et al, 2000;, we can define the extent of intervention of each lithology in the final mixture based on other features.…”
Section: Provenance and Geotectonic Settingsupporting
confidence: 67%
See 1 more Smart Citation
“…Comparing these data with the average values obtained by Palomares and Arribas (1993) for different mixed source ar- rocks (Table 2) indicates a mixed composition source area (Mack, 1981). However, as several authors have suggested (Palomares and Arribas, 1993;Le Pera and Arribas, 2004), the abundance of these grains in the sediments is not directly related to their abundance in the source area. Even when each lithology have a different Sand Generation Index (Palomares and Arribas, 1993;Arribas et al, 2000;, we can define the extent of intervention of each lithology in the final mixture based on other features.…”
Section: Provenance and Geotectonic Settingsupporting
confidence: 67%
“…Several studies have addressed the relationship between climate and sandy deposit composition in present-day sediments Basu, 1976;Suttner et al, 1981;Franzinelli and Potter, 1983) which serves as a base for palaeoclimatic interpretations of older sediments. To better understanding the roles of these factors in determining sand composition, actualistic research has addressed fluvial to transitional and marine deposits worldwide (Ingersoll and Suczek, 1979;Le Pera and Critelli, 1997;Le Pera et al, 2001) including river sediments of the Madrid Basin (Arribas et al, 2000;Le Pera and Arribas, 2004). This paper addresses sand petrofacies formed during the Middle Aragonian (14.2Ma) at the Somosaguas palaeontological site (Madrid Basin), the evolution of their source area (Spanish Central System) and the climate that prevailed over the middle Miocene in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Petrographic investigation of sandstone is widely used to infer tectonic setting, source rock composition, transportation and environment of deposition (Dickinson 1970(Dickinson , 1985Dickinson and Suczek 1979;Dickinson et al 1983;Ingersoll and Suczek 1979;Le Pera and Arribas 2004;Le Pera et al 2001;Zuffa 1985Zuffa , 1987. Sediments derived from cratonic sources (low-lying, granitic or gneissic with recycled platform sediments) are generally quartzose sands with high monocrystalline quartz (Qm)/polycrystalline quartz (Qp) and K-feldspar (K)/plagioclase feldspar (P) ratios, and deposited in continental interiors or passive continental margins (Dickinson 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the low percentage of slate-schist fragments (b2%), the presence of these rock fragments is highly significant. Several studies on modern sediments (Palomares and Arribas, 1993;Le Pera and Arribas, 2004) have demonstrated that sandstone composition does not allow direct quantitative estimations of the lithologies at the source, owing to the different capacities of rocks to generate sands (Palomares and Arribas, 1993). Indeed, slates and schists show a very low sand-generating capacity (Sand Generation Index, Palomares and Arribas, 1993) and are often underrepresented, because of their low rock-fragment content.…”
Section: Discussionmentioning
confidence: 99%